تكنولوجيا المعلومات أساس تطويرالمعرفة وذكاء الأعمال - يحياوي, مفيدة; قروش, عيسى (جامعة الوادي - University of Eloued, 2013)
إن الجدل حول التكنولوجيات الحديثة بالتوافق مع أنظمة المعلومات هي الضرورة الأولى في المعطى الاقتصادي الجديد، إذ أن تكنولوجيا المعلومات تلعب دورا حيويا ضمن هذه التحولات العميقة، فظهور وانتشار هذه التكنولوجيا جعل المؤسسات تطبقها في عدة ميادين كميدان التسويق والإنتاج وغيرهما.بفضل التطور السريع والمستمر للتكنولوجيا، فان الوصول إلى المعلومات أصبح بشكل أسهل بكثير، وذلك دون شك واحدة من الخصائص الرئيسية للمجتمع ألان. فذكاء الأعمال يسعى للاستفادة من هذا الوضع من خلال تطوير الأساليب التي تسمح بتحديد مصادر المعلومات الناجعة، وتحليلها وجمعها وتحويلها إلى المعرفة لمساعدة عملية صنع القرار.من خلال المعلومات المتاحة من خارج الشركة، فان ذكاء الأعمال يغطي مناطق واسعة من التكنولوجيا إلى الأسواق ثم إلى اللوائح. اليوم، إن البطء في نشر أساليب وأدوات ذكاء الأعمال لا يخفي الطاقة الهائلة من الإبداع والابتكار الذي يحتويه.كما أن ذكاء الأعمال يرتبط ارتباطا وثيقا بمفاهيم أخرى مثل إدارة المعرفة التي تتمثل في العمل بالمعلومات المتاحة داخل الشركة واستخدام البرمجيات المناسبة لإدارة المعلومات الكمية. the debate on new technologies, in this case information systems, is essential in the new economic situation, because information technologies play a key role in the deep-seated changes that we are trying to make. apply to forecasting methods, the deployment and emergence of IT has allowed the rapid spread of these technologies in the field of Marketing. Thanks to the rapid and continuous development of technologies, access to information is now greatly facilitated and is undoubtedly one of the major characteristics of the society that is created every day before us. Business Intelligence aims to take advantage of this situation by developing methods that identify relevant sources of information, analyze the information collected and transform it into knowledge to aid decision-making. Turning to information available outside the company, business intelligence covers broad areas of interest, from technology to the market or regulation. Today, the slow diffusion of the methods and tools of the business intelligence must not mask the formidable potential of innovation that it generates. Business intelligence is also closely linked to other concepts such as knowledge management - which consists of working with the information available within the company and the use of appropriate software to manage quantitative information.
مقال
Keywords: تكنولوجيا المعلومات، الذكاء الصناعي، بيئة الأعمال